Depression, Anxiety, Stress, and Their Associations With Quality of Life in a Nationwide Sample of Psychiatrists in China During the COVID-19 Pandemic - Li, Mengdie; Xia, Lei; Yang, Yating; Zhang, Ling; Zhang, Shujing; Liu, Tingfang; Liu, Yuanli; Kaslow, Nadine J.; Jiang, Feng; Tang, Yi-lang; Liu, Huanzhong (Frontiers in Psychology, 2022)
Abstract Objectives: The COVID-19 pandemic has negatively affected well-being. However, the impact on the mental health status and quality of life (QOL) in psychiatrists in China has not been examined. Methods: This was a national cross-sectional survey performed between January 11 and March 15, 2021. Demographic and work-related data were collected anonymously using an online questionnaire. Common mental health symptoms and QOL were assessed using the Depression Anxiety Stress Scale-Chinese version and the World Health Organization Qual-ity of Life Schedule-Brief respectively. Results: A total of 3783 psychiatrists completed this questionnaire. The prevalence of de-pressive, anxious and stress symptoms were 26.7% (95%CI=25.3-28.1%), 24.1% (95%CI=22.8-25.5%), and 11.6% (95%CI=10-12%), respectively. 11.1% endorsed both depressive and anxious symptoms and 8% endorsed symptoms in all three domains. Binary logistic regression showed that aged 30-39 (OR=1.5, P=0.03), male gender (OR=1.2, P=0.04), single (OR=1.44, P=0.01), negative perceived impact of the COVID-19 on healthcare (OR=2.34, P<0.001) were more inclined to experience depressive symptom. Participants who divorced and widowed (OR=1.56, P=0.03), more than 4 night shifts/month (OR=1.33, P<0.001), longer working years (OR=1.71, P<0.001), negative perceived impact of the COVID-19 on healthcare (OR=2.05, P<0.001) were more inclined to experience anxious symptom. In addition, psychiatrists with high QOL scores had lower odds of experiencing depressive, anxious and stress symptoms (all P<0.001). Multivariate analysis showed that the presence of each of the three types of mental health symptoms was independently associated with lower QOL (all P<0.05). In addition, the depres-sionanxiousstress interaction was significantly correlated with lower QOL (P<0.05). Conclusion: Approximately one fourth of psychiatrists in China experienced depressive and anxious symptoms during the COVID-19 pandemic, and more than one tenth reported stress. Mental health symptoms were significant contributors to lower QOL. The psycho-logical well-being of psychiatrists during the pandemic requires more attention, and interventions are needed to improve the psychological well-being of physicians who care for individuals with mental disorders.